RELEVANSI NILAI-NILAI CANAKYA NITI SASTRA TERHADAP PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI METODE BERCERITA DI TK NEGERI CITRA WIDYA - Terijayanti, Ni Putu Oka (UHN IGB Sugriwa Denpasar, 2026)
This study aims to examine the relevance of moral values ​​in Canakya Niti Sastra to the character formation of early childhood through storytelling methods in Citra Widya State Kindergarten. The background of the study is based on the importance of character education from an early age and the need for universal and contextual sources of values. This study uses a qualitative approach with descriptive methods. Data collection techniques include observation of learning activities, interviews with teachers, and documentation. The focus of the study is directed at three main aspects, namely the relevance of Canakya Niti Sastra's moral values ​​to the character formation of early childhood, story development strategies based on Canakya Niti Sastra values ​​that are appropriate to children's learning characteristics, and the application of storytelling methods in instilling these values ​​in learning. The results of the study indicate that moral values ​​in Canakya Niti Sastra, such as honesty, responsibility, discipline, self-control, and mutual respect, have strong relevance to the goals of character formation of early childhood. The story development strategy is carried out by adapting the substance of the values ​​into a simple storyline that is close to children's experiences, so that it is easy to understand and internalize. The application of the storytelling method has proven effective in increasing children's moral understanding, emotional involvement, and positive behavioral changes in everyday life. Thus, the storytelling method based on the values ​​of Canakya Niti Sastra can be used as an alternative, contextual and meaningful character education strategy for early childhood. Keywords: Canakya Niti Sastra, character education, storytelling method, early childhood.